2004
DOI: 10.1002/ijc.20010
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin, an inhibitor of the chaperone activity of HSP90, induces MAPK‐independent cell cycle arrest

Abstract: The effects of GA, an ansamycin antibiotic in development as a lead anticancer drug, were studied in mouse BP-A31 fibroblasts and in human cancer-derived cell lines. GA and related molecules act by inhibiting the chaperone function of the Hsp90 protein through competition for ATP binding. The antiproliferative effects of GA have been attributed to destabilization of the Raf-1 protein, one of the targets of Hsp90, and to the resulting inhibition of MAPK. Addition of GA to BP-A31 cells, synchronously progressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 58 publications
0
34
0
1
Order By: Relevance
“…Yim et al showed that, in DU-145 cells, treatment with high micromolar concentrations of a coumarin compound decursin yielded a decrease in cdk 2, cdk 4, cdk 6, and cyclin D1 expression and a reduction of percentage of cells in S-phase (31). Similar data were obtained in DU-145 cells with the antibiotic geldanamycin, a drug whose target is the chaperone heat shock protein 90 (32). At present, molecular mechanism of the geldanamycin effect, in particular requirement of functional tumor suppressor retinoblastoma, is not fully understood (33).…”
Section: Discussionmentioning
confidence: 56%
“…Yim et al showed that, in DU-145 cells, treatment with high micromolar concentrations of a coumarin compound decursin yielded a decrease in cdk 2, cdk 4, cdk 6, and cyclin D1 expression and a reduction of percentage of cells in S-phase (31). Similar data were obtained in DU-145 cells with the antibiotic geldanamycin, a drug whose target is the chaperone heat shock protein 90 (32). At present, molecular mechanism of the geldanamycin effect, in particular requirement of functional tumor suppressor retinoblastoma, is not fully understood (33).…”
Section: Discussionmentioning
confidence: 56%
“…WP1130-induced degradation of Bcr/Abl is independent of the Hsp90/Hsp70 pathway, which engages a proteasomal-dependent mechanism for Bcr/Abl down-regulation by geldanamycin. 38,39 By targeting the Bcr/Abl protein through a distinct mechanism, WP1130 has an advantage over imatinib mesylate in that its activity is not inhibited by a variety of Abl kinase mutations, including T315I ( Figure 3A). We found that WP1130 strongly inhibited the growth of cell lines expressing either wild-type or the T315I mutant form of Bcr/Abl as well as leukemic blast progenitor cells from patients who had developed imatinib mesylate-resistant CML blast crisis ( Figure 3D).…”
Section: Discussionmentioning
confidence: 99%
“…The benzoquinone ansamycin antibiotic geldanamycin binds strongly to Hsp90 and competes for ATP binding, disrupting its chaperone activity. 38 Inactivation of Hsp90 is followed by an increase in Hsp70 expression and a shift in the binding of Bcr/Abl from Hsp90 to Hsp70, 39 which reduces the stability of Bcr/Abl. To assess the possible involvement of an Hsp90/Hsp70 mechanism in the action of WP1130, we compared the effects of WP1130 and geldanamycin on Bcr/Abl downregulation.…”
Section: Mechanism Of Wp1130-induced Bcr/abl Down-regulationmentioning
confidence: 99%
“…GA induced G1 arrest associated with decrease of both total and Cdk2-associated cyclin E, as well as partial reduction of Cdk4 in mouse fibroblast (Bedin et al 2004). In prostate cancer cell lines, 17-AAG caused the degradation of HER2, Akt, and androgen receptor, both wild and mutant forms, resulting in G1 arrest (Solit et al 2002).…”
Section: Discussionmentioning
confidence: 99%